Preparation and electrical properties of nanocrystalline BCNO - Posak Tippo (2018)
© 2017 Elsevier B.V. We reported a synthesis of quaternary B-C-N-O alloys containing boron, carbon, nitrogen, and oxygen atoms by using melamine-boric acid adduct colloidal solutions (C3N6H6·2H3BO3) as a precursor via chemical reactions. The nanocrystalline BCNO was observed by scanning electron microscope. Results from X-ray diffraction show a prominent peak at 28.13° for BCNO, indicating the interlayer distance of 0.317 nm. Elemental compositions and chemical bonds of BCNO were verified by X-ray photoemission spectroscopy. Electrical measurement of BCNO-based field effect transistors gave 0.3 cm2V−1s−1of charge mobility, 0.77 eV of band gap with 105of on/off ratio.